Factors influencing the purchasing decision of Assam tea among individuals in Chiang Mai Province - pinta, ladda; Asakit, Haruethai (Journal of Industrial Business Administration, 2024)
This study aims to investigate the factors influencing the purchasing decisions of Assam tea among the population in Chiang Mai province. The study includes a population and sample group, of individuals who have previously purchased Assam tea in Chiang Mai, totaling 400 participants.Convenience sampling was used as the sampling method, with participants randomly selected until reaching the target of 400 samples. The data collection tool used was a questionnaire, and statistical methods such as percentages, averages, frequency distribution, standard deviation, and simple linear regression analysis, were employed for data analysis. Multiple regression was used to search for predictive factors, and a predictive equation was created using the Enter method. The research findings indicatethat themajorityof respondents to the questionnaire are male, aged 16-26, with undergraduate education, and a monthly income of less than 10,000 baht. Most of them purchase herbal tea,specifically green tea, black tea, and Assam tea., from grocery stores, water stalls, and floating markets.with an expenditure of less than 100 baht per purchase. In terms of marketing mix factors, productrelated factors were rated at the highest level, followed by distribution channels, price factors, and marketing promotion factors. Regarding attitude factors, the overall level was high. with knowledge and understanding factors at the highest level, followed by emotional factors, feelings, and behavioral factors, respectively, this study also found that deciding to buy Assam is important to consumers.If consumers have a positive attitude towards any brand of tea, they will decide to buy it immediately.